2019
DOI: 10.1088/1757-899x/584/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Factors effecting on the compressive and tensile strength of reactive powder concrete made with local materials

Abstract: Ultra High Performance Concrete (UHPC) represent as one of the most concrete progressive development so that it can be improved the strength, durability, reliability, and resilience of the concrete structures. The availability of local materials play the main role in the major step in making the economic mix jobs by saving their materials and effort and decrease the concrete cost. So in this paper, the parameters including the curing regimes, of sand gradation, binder type, and content, and steel fiber content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…66 or 6% by volume in the studies of Pourbaba et al, 65 Abbas et al, 8 and Nehdi et al 56 Nevertheless, any fiber dosage exceeding 5% by volume tended to have a negative impact on the economic aspect of concrete, so this value was selected as the upper limit in this cost evaluation. Table 5 and Figure 11 presented a cost estimation of several existing mix designs 8,17,51,66,[85][86][87] based on their components. The contribution of steel fiber to the total expense of concrete varied in a very wide range which was from 6% to 106% of non-fiber concrete costs.…”
Section: Cost Of Concrete MIXmentioning
confidence: 99%
See 3 more Smart Citations
“…66 or 6% by volume in the studies of Pourbaba et al, 65 Abbas et al, 8 and Nehdi et al 56 Nevertheless, any fiber dosage exceeding 5% by volume tended to have a negative impact on the economic aspect of concrete, so this value was selected as the upper limit in this cost evaluation. Table 5 and Figure 11 presented a cost estimation of several existing mix designs 8,17,51,66,[85][86][87] based on their components. The contribution of steel fiber to the total expense of concrete varied in a very wide range which was from 6% to 106% of non-fiber concrete costs.…”
Section: Cost Of Concrete MIXmentioning
confidence: 99%
“…Table 5 and Figure 11 presented a cost estimation of several existing mix designs 8,17,51,66,85–87 based on their components. The contribution of steel fiber to the total expense of concrete varied in a very wide range which was from 6% to 106% of non‐fiber concrete costs.…”
Section: Evaluation Of Materials Costmentioning
confidence: 99%
See 2 more Smart Citations
“…They found the use of fly ash and nano-silica enhanced the compressive strength, and the percentage of silica foam ranges from 0.15% to 0.3%. Chkheiwer and Kadim [21] studied the effect of silica fume ratio, steel fiber percentage, curing, and sand gradation on the properties of RPC made with locally available materials. It was found that the optimum percentage of silica fume was 25% of the total weight of the binder.…”
Section: Introductionmentioning
confidence: 99%